Розробка технології виробництва питного молока із застосуванням струминного та пульсаційного гомогенізаторів - Кюрчев, Сергій Володимирович; Самойчук, Кирило Олегович; Ломейко, Олександр Петрович; Kiurchev, Serhii; Samoichuk, Kyryl; Lomeiko, Oleksandr (Запоріжжя : 2024, 2024)
UA: Для підвищення енергоефективності процесів виробництва питного молока необхідно вирішити проблему високих енерговитрат на процес гомогенізації. Для цього запропоновано впровадження енергоефективних струминних та пульсаційних гомогенізаторів. Але для їх використання підприємствами важливим етапом є коригування існуючої технологічної схеми виробництва молока та перевірка її ефективності експериментальним шляхом. Розробка технологічних схем виробництва питного молока із застосуванням розроблених гомогенізаторів повинна включати вибір режимних і технологічних параметрів роботи кожного типу гомогенізатора. Для того, щоб розробити технологію переробки молока з використанням цих двох гомогенізаторів, необхідно встановити взаємозв'язок між режимами роботи клапанних гомогенізаторів та основними параметрами нових гомогенізаторів. Перевірка якості виробленого молока здійснювалась за основними показниками, які передбачають діючі стандарти та показала повну відповідність виробленого харчового продукту сучасним вимогам. EN: To increase the energy efficiency of drinking milk production processes, it is necessary to solve the problem of high energy consumption for the homogenization process. For this purpose, the introduction of energy-efficient stream and pulsating homogenizers is proposed. But for their use by enterprises, an important step is to adjust the existing technological scheme of milk production and check its effectiveness experimentally. The purpose of this article is to develop a new technology for the production of drinking milk using jet and pulsating homogenizers. To achieve the goal, the article establishes the sequence of technological operations for the production of drinking milk using jet and pulsation homogenizers. Regime parameters of technological operations for the production of drinking milk using jet and pulsating homogenizers have been established. The list of technological operations of new technological schemes for the production of drinking milk include: evaluation of the quality of raw materials, reception of milk, its cooling, storage, cleaning, homogenization, pasteurization, cooling, inspection of the quality of the finished product, packaging, packaging and labeling and storage. Batches of drinking milk were produced using the developed technological schemes and checked for compliance of its quality with existing standards in Ukraine. Batches of dairy products were produced using the developed homogenizers. As a result of the analyzes carried out in the department of analytical research and quality of food products of the Institute of Food Resources of the National Academy of Sciences of Ukraine, it was established that according to organoleptic indicators: appearance and consistency, taste, smell and color, the produced drinking milk fully meets the standards. Bacteria and microorganisms, the content of which is not allowed by the current standards in the manufactured batches of the product, were not detected. Separately, it is necessary to highlight the fluctuations of the fat content of milk, according to which normalization was carried out in the jet homogenizer. This value did not exceed +0.05 -0.07%. That is, the accuracy of normalization is high. Drinking milk produced in this way fully complies with current norms and standards and can be recommended for production.
Development of drinking milk production technology using stream and pulsation homogenizers
Keywords: гомогенізація; питне молоко; струминний гомогенізатор; пульсаційний гомогенізатора; технологія; технологічна схема; homogenization; drinking milk; stream homogenizer; pulsation homogenizer; technology; technological scheme